2022
DOI: 10.1021/acsami.2c18120
|View full text |Cite
|
Sign up to set email alerts
|

Additive Engineering of the CuSCN Hole Transport Layer for High-Performance Perovskite Semitransparent Solar Cells

Abstract: CuSCN has been widely considered a promising candidate for low-cost and high-stable hole transport material in perovskite semitransparent solar cells (STSCs). However, the low conductivity of the solution-processed CuSCN hole transport layer (HTL) hinders the hole extraction and transport in devices, which makes it hard to achieve devices with high performance. Herein, we report a facile additive engineering approach to optimize the p conductivity of CuSCN HTLs in perovskite STSCs. The n-butylammonium iodide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 30 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…The PCE of devices based on the CuSCN HTL layer is highly sensitive at lower values of both μ h and N A and saturates beyond certain minimum values (μ h > 10 –4 cm 2 V –1 s –1 and N A > 10 17 cm –3 ). These values are quite achievable in CuSCN thin film without doping as in the current investigation and reported elsewhere. , Furthermore, a comparison table of reported simulations of planar Sb 2 S 3 solar with different device structures is presented in Table S2. The device with a CuSCN HTL in the ideal case (low bulk defect density of 10 12 cm –3 and no interface traps) should theoretically perform as well as other HTLs.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The PCE of devices based on the CuSCN HTL layer is highly sensitive at lower values of both μ h and N A and saturates beyond certain minimum values (μ h > 10 –4 cm 2 V –1 s –1 and N A > 10 17 cm –3 ). These values are quite achievable in CuSCN thin film without doping as in the current investigation and reported elsewhere. , Furthermore, a comparison table of reported simulations of planar Sb 2 S 3 solar with different device structures is presented in Table S2. The device with a CuSCN HTL in the ideal case (low bulk defect density of 10 12 cm –3 and no interface traps) should theoretically perform as well as other HTLs.…”
Section: Resultssupporting
confidence: 75%
“…To further investigate the improvement of device performance (especially the V OC ), surface potentials suggesting a p-type character with high carrier density (>10 17 cm −3 ). 50 Another important attribute of employing CuSCN with a high E F (and E v ) is the elimination of the Fermi-level pinning phenomenon. Savadogo and Mandal 67 reported that the Schottky barrier height was independent of the work function of the top contact and concluded the Fermi level was pinned near the midgap of Sb 2 S 3 (around −4.5 eV).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…As in previous work, the structure of ST-PSC is composed of ITO/SnO 2 /perovskite/HTL/MoO x /ITO, as shown in Fig. S21 † 34 . This ST-PSC yields a high PCE of 19.35% with a V OC of 1.14 V, a J SC of 21.29 mA cm −2 , and an FF of 79.43% in Fig.…”
Section: Resultsmentioning
confidence: 81%
“…It has been reported that CuSCN-based devices are more stable in an air atmosphere than their Spiro-OMeTAD counterparts. 44 In 2017, Gratzel's group developed CuSCN HTL-based opaque PSCs that had a PCE of 20% and much better stability than Spiro-OMeTAD-based PSCs. 45 Furthermore, CuSCN doped with p-type elements could result in reduced trap state density and vacancy defects, thereby improving thermal resistance and preventing elemental interdiffusion, which is advantageous to improving the device's thermal stability.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its wide bandgap (3.7–3.9 eV), it transmits light throughout the visible and near-infrared spectrum. , Furthermore, β-CuSCN manifests good stability and high mobility of 0.01–0.1 cm 2 V –1 s –1 compared to its counterpart, Spiro-OMeTAD (∼10 –3 cm 2 V –1 s –1 ). It has been reported that CuSCN-based devices are more stable in an air atmosphere than their Spiro-OMeTAD counterparts . In 2017, Gratzel’s group developed CuSCN HTL-based opaque PSCs that had a PCE of 20% and much better stability than Spiro-OMeTAD-based PSCs .…”
Section: Introductionmentioning
confidence: 99%